Regional Mechanisms for Protecting Women's Rights: An Analytical Study of European, American, African, and Arab Conventions - Aman Ahmed Almutturdy (Journal of Scientific and Human Dimensions, 2026)
This research examines the pivotal role of regional international organizations—namely European, American, African, and Arab entities—in establishing and safeguarding women's rights through specialized legal mechanisms and conventions. By adopting a multifaceted methodology that integrates historical tracking, descriptive analysis, and analytical evaluation, the study explores the foundations of regional protection and the guarantees provided to enhance women’s status while respecting cultural and social specificities. The paper details key instruments such as the European Convention on Human Rights, the American Convention on Human Rights, the African Charter, and the Arab Charter on Human Rights, alongside the judicial and semi-judicial roles of regional courts and commissions. Furthermore, it evaluates scientific efforts and institutional initiatives, such as those by the Arab Women Organization, aimed at aligning regional protections with global development and social peace, ultimately offering recommendations to strengthen legislative frameworks and promote a culture of gender equality.
Keywords: Protection of Women's Rights; Regional Organizations; International Regional Protection Means